When contact goes wrong: Negative intergroup contact promotes generalized outgroup avoidance. (August 2019) - Meleady, Rose; Forder, Laura
This paper broadens our understanding of the consequences of negative intergroup contact. Study 1 reports cross-sectional evidence that negative contact with European immigrants in Britain is not only associated with increased prejudice, but also the avoidance of future contact with this group. Studies 2A and 2B provided an experimental replication in a different intergroup context. A negative encounter with an outgroup member, but not an ingroup member, was found to reduce intentions to engage in contact with the outgroup in the future. Study 3 went on to demonstrate that the effect of negative contact on outgroup avoidance is not limited to the contacted outgroup, but is indirectly associated with reduced intentions to engage with other, secondary outgroups—an effect we refer to as avoidance generalization effect . Negative contact was also associated with lower general contact self-efficacy. Together, findings suggest that negative contact is damaging not just because it increases prejudice but also because it compromises future engagement with diversity.